Human Sensorimotor Activity as a Factor of Cognitive Resource Development - Balanev, D. Yu; Tyutyunnikov, P. R.; Kokh, D. A. (Вестник Кемеровского государственного университета, 2022)
The cognitive resource phenomenon, its factors, and performance are a relevant topic of Russian psychology. Numerous publications feature the psychological content of the cognitive resource concept and various phenomena as forms of its manifestation. However, domestic psychology sees no cognitive resource potential in sensorimotor activity, nor does it see sensorimotor activity as a factor that facilitates human cognitive resources. The article considers sensorimotor activity as a cognitive resource and describes a transspective analysis of various approaches to the phenomenon of cognitive resource. The authors defined the latter as a complex multi-level construct. Various cognitive resource models proved that sensorimotor activity is a manifestation of the cognitive resource and its integral part. However, the transspective analysis requires further research on sensorimotor activity in the cognitive resource structure.